The Relationship Between Work Posture and Work Period with Musculoskeletal Disorders (MSDs) Complaints in Nurses in the Emergency Room (IGD) at Gambiran Hospital, Kediri City - Natalinggit Pingkan Anyelir; Nafilatul Fitri; Fresvian Jenrivo; Rizki Mustika Riswari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Many patient care activities and carried out for a long duration of time can trigger nurses to not realize that every movement they make has the potential for incorrect or abnormal postures. Infusion installation and wound care activities that are not ergonomic, such as standing with your back bent and your neck statically bent for long periods of time, have the potential to cause complaints of Musculoskeletal Disorders (MSDs). The longer of working period, the higher of potential for experiencing Musculoskeletal Disorders (MSDs) complaints. Objective: Determine the description of Musculoskeletal Disorders (MSDs) complaints, the relationship between work posture and Musculoskeletal Disorders (MSDs) complaints and the relationship between work experience and Musculoskeletal Disorders (MSDs) complaints. Method: This type of research is quantitative with a total sampling technique. Data collection was carried out with the Nordic Body Map (NBM) questionnaire instruments and the Rapid Entire Body Assessment (REBA) form on 34 emergency room nurses at RSUD Gambiran Kota Kediri. Result: the majority of nurses had a moderate level of work posture risk and have a long service life (> 6 years). The most common complaints experienced by nurses are in the right shoulder, back and waist. Based on the hypothesis test, working posture with complaints of Musculoskeletal Disorders (MSDs) was found to be (p-value 0.033) < 0.05 and work period with complaints of Musculoskeletal Disorders (MSDs) was obtained (p-value 0.048) < 0.05. Conclusion: there is a significant relationship between work posture and complaints of Musculoskeletal Disorders (MSDs) and a significant relationship between work period and complaints of Musculoskeletal Disorders (MSDs).